The Effectiveness of Enterprise Risk Management and Internal Audit Function on Quality of Financial Reporting in Universities - N, Wadesango; C., Mhaka (Journal of Economics and Behavioral Studies, 2017)
This study examined the impact of enterprise risk management (ERM) and internal audit function (IAF) on the financial reporting quality (FRQ) of state universities in Zimbabwe. Utilizing a dataset of 250 respondents from across nine (9) state universities, the researchers examined the effectiveness of ERM and the IAF on the quality of financial reporting in state universities. The researchers employed the contingency theory and studied each university separately to report on items that are specific to each and then also establish a commonality in the definition of parameters to be used in setting up the benchmark against which future performance may be measured. The findings were that there is a strong and significant relationship between ERM and the FRQ and also that there is a positive relationship between the internal audit function and FRQ. Quality internal audit results improved corporate governance systems. The results also underscore the significance and need for central government to establish and monitor a system of good ERM processes that minimize corporate governance breaches and enhance integrity and independence in financial reporting in state universities.